Optimised sensor configurations with reduced order controllers applied to an EMS system - Michail, K; Yimin Zhou; Zolotas, A; Goodall, R; Halikias, G (Proceedings of the 29th Chinese Control Conference, 2010)
In many applications, sensor selection in an optimum sense is not a trivial task, especially when a number of objectives and constraints are to be satisfied simultaneously. Moreover, for practical implementation the order of the synthesized controller could be a burden of increased cost and complexity. In this paper, a systematic framework for optimum sensor selection is considered which considers issues of controller reduction. Efficacy of the proposed framework is illustrated via simulations on an Electro-Magnetic Suspension (EMS) system.